Comparison of synergistic effects of multiple combinations of anti-pseudomonas antibiotics against Pseudomonas aeruginosa pan drug resistance in in vitro test with AZDAST Method - Putri, Citra Destya Rahma; Etty Fitria Ruliatna; Retnoningsih, Dewi; Rahayu, Siwipeni Irmawanti; Noorhamdani (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Background: Antimicrobial resistance is a global threat to public health. Pseudomonas aeruginosa Pan Drug-Resistant requires the latest antimicrobials. This limitation of therapy requires a breakthrough in the treatment of this infection. Combining antimicrobials with a synergistic effect is thought to increase the cure rate in clinical use. This study aimed to determine the synergistic effect of several combinations of anti-pseudomonas antibiotics against Pan Drug-Resistant Pseudomonas aeruginosa in an in vitro test using the AZDAST method. Method: An Antibiotic combination test was carried out using the AZDAST method to assess in vitro synergistic activity. The antibiotic single disk used was Amikacin 30 µg, Ceftazidime 30 µg, Meropenem 10 µg, Ciprofloxacin 5 µg; double disk antibiotic is Amikacin 30 µg, Ceftazidime 30 µg, Meropenem 10 µg, Ciprofloxacin 5 µg and combination antibiotic disks Amikacin 30 µg-Ceftazidime 30 µg, Amikacin 30 µg-Meropenem 10 µg, Amikacin 30 µg-Ciprofloxacin 5 µg in which two antibiotic paper disks are combined stacked together, with a 24 mm gap between the other antibiotic combinations. Result: The results showed that combining the four antibiotics had a synergistic effect. The zone of inhibition resulting from testing the combination of several antibiotics against Pan Drug Resistant Pseudomonas aeruginosa showed no statistical significance (p > 0.05) compared to all antibiotics and comparisons in the combination group of antibiotics only. Conclusion: The combination of anti-pseudomonas antibiotics synergizes with Pan Drug-Resistant Pseudomonas aeruginosa in the AZDAST method in vitro test.